Islam and customary law: Iddah for husbands after divorce in South Tapanuli Regency - Sainul, Ahmad (Asy-Syari’ah : Jurnal Hukum Islam, 2025)
This article aims to describe the phenomenon of the implementation of iddah for husbands after divorce in South Tapanuli Regency. Field studies using juridical-sociological as the approach. The primary data source of this study is the results of interviews with traditional leaders, religious leaders and husbands who carry out iddah after divorce. Secondary data sources are in the form of the Compilation of Islamic Law, books, journals, and other materials relevant to this study. This study was analyzed using a descriptive approach. The results of the study show that the phenomenon of iddah for husbands after divorce in South Tapanuli Regency only regulates the time when husbands are allowed to remarry. During the iddah period, there is no prohibition on dressing up, using perfume, and leaving the house. The length of the husband's iddah a ccording to South Tapanuli Custom is adjusted to the iddah of his ex-wife. However, the majority of the time required for the iddah period is longer because permission must be obtained from the wife's family or in-laws.